2022
DOI: 10.1186/s13018-022-03086-5
|View full text |Cite
|
Sign up to set email alerts
|

Determining the accuracy of preoperative total hip replacement 2D templating using the mediCAD® software

Abstract: Background Templating is a preoperative planning procedure that improves the efficiency of the surgical process and reduces postoperative complications of total hip arthroplasty (THA) by improving the precision of prediction of prosthetic implant size. This study aimed to evaluate the accuracy of the preoperative cup and stem size digital 2D templating of THA with mediCAD® software and find the factors that influence the accuracy, such as indication for surgery, patients’ demographics, implant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 33 publications
(48 reference statements)
0
6
0
Order By: Relevance
“…PO angle was measured as the angle between the horizontal plane and the inter-teardrop line (Fig. 4) [5] using mediCAD ® software (version 3.5, Hectec, Landstuhl, Germany) [9]. Heidt et al compared the variations of the O'Brien method and revealed that the angle formed by the horizontal reference line and the inter-teardrop line was most reliable for measuring pelvic obliquity [7].…”
Section: Methodsmentioning
confidence: 99%
“…PO angle was measured as the angle between the horizontal plane and the inter-teardrop line (Fig. 4) [5] using mediCAD ® software (version 3.5, Hectec, Landstuhl, Germany) [9]. Heidt et al compared the variations of the O'Brien method and revealed that the angle formed by the horizontal reference line and the inter-teardrop line was most reliable for measuring pelvic obliquity [7].…”
Section: Methodsmentioning
confidence: 99%
“…Hemispherical porous-coated Trilogy cups (Zimmer, Inc.) and porous-coated Pinnacle cups (DePuy Orthopaedics, Inc.) were used for the acetabular component. 2D templating was performed on all patients before surgery using mediCAD software 29 . The perioperative care was the same for TKA patients described above, except THA patients did not receive cocktail injections and oxycodone.…”
Section: Methodsmentioning
confidence: 99%
“…In short, the surgeon must adjust the prosthesis model and its position according to his/her own experience, thereby extending the operation time and increasing the risk of bleeding and infection. [ 9 , 10 ] Three-dimensional (3D) preoperative planning based on computed tomography (CT) data (e.g., Mimics, MAKO, and ZedHip) is thought to improve the accuracy of prosthesis placement and reduce surgical complications;[ 11 , 12 ] however, this method is limited in terms of the complicated planning steps and the time involved, restricting its clinical application.…”
Section: Introductionmentioning
confidence: 99%